Observations of bears in relation to onset of the early big-game hunting and variations in pine cone production in Gardiner Ranger District, Montana - Hermansson, Pär (SLU/Dept. of Ecology, 2010)
The early big game hunt in hunting district 316 (HD 316) on the Gardiner Ranger District, south west Montana USA, takes place within the Primary Conservation Area for the Yellowstone grizzly bear (Ursus arctos horribilis). Outside of the hunting season, HD 316 is also a popular area for hiking, horseback riding and camping during the whole bare ground season. The hunting activity has been an object for concern due to increased grizzly bear mortality. The mortality is mainly related to conflicts between hunters and bears (usually grizzlies) and the reason for the conflicts points towards the scattered remains from harvested ungulates. Years when the cone production of whitebark pine (Pinus albicaulis) is low have shown an increase in these human-bear conflicts in the Greater Yellowstone Area (GYA). The purpose of this study is to: